The Intron Retention Variant CsClpP3m Is Involved in Leaf Chlorosis in Some Tea Cultivars - Luo, Xueyin; Zhang, Mengxian; Xu, Pei; Liu, Guofeng; Wei, Shu (Frontiers in Plant Science, 2022)
Tea products made from chlorotic or albino leaves are very popular for their unique flavor. Probing into the molecular mechanisms underlying the chlorotic leaf phenotype is required to better understand the formation of these tea cultivars and aid in future practical breeding. In this study, transcriptional alterations of multiple subunit genes of the caseinolytic protease complex (Clp) in the chlorotic tea cultivar ‘Yu-Jin-Xiang’ (YJX) were found. Cultivar YJX possessed the intron retention variant of ClpP3, named as CsClpP3m, in addition to the non-mutated ClpP3. The mutated variant results in a truncated protein containing only 166 amino acid residues and lacks the catalytic triad S182-H206-D255. Quantitative analysis of two CsClpP3 variants in different leaves with varying degrees of chlorosis in YJX and analyses of different chlorotic tea cultivars revealed that the transcript ratios of CsClpP3m over CsClpP3 were negatively correlated with leaf chlorophyll contents. The chlorotic young leaf phenotype was also generated in the transgenic tobacco by suppressing ClpP3 using the RNAi method; complementation with non-mutated CsClpP3 rescued the wild-type phenotype, whereas CsClpP3m failed to complement. Taken together, CsClpP3m is involved in leaf chlorosis in YJX and some other tea cultivars in a dose-dependent manner, likely resulting from the failure of Clp complex assembly due to the truncated sequence of CsClpP3m. Our data shed light on the mechanisms controlling leaf chlorosis in tea plants.